Роман Ф. М. Достоевского "Преступление и наказание": комментарий : книга для учителя / С. В. Белов - Белов Сергей Владимирович (Просвещение, 1985)
Экземпляры: аб. ЦБ (1985) / Инвентарный номер: 13730 / Сис.шифр: 83.3(2Рос=Рус)1 / Авт.знак: Б 43 / ББК: 83.3(2Рос=Рус)1